Tinjauan Maqasid Syariah terhadap Penolakan Hakim dalam Gugatan Hak Asuh Anak bagi Ayah ataupun Ibu - Putra Ramadan; Badrul Munir; Aulil Amri (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The implementation of maqasid al-shariah in child custody cases at the Banda Aceh Sharia Court reflects a paradigm shift from a textual application of Islamic law toward a contextual approach that prioritizes the welfare of the child. The analysis of three judicial decisions reveals that judges integrate the principles of protecting life (hifz al-nafs), lineage (hifz al-nasl), and intellect (hifz al-‘aql) into their legal reasoning. This interpretive approach produces a balance between normative and substantive justice, portraying Islamic law as a humane and context-sensitive system within the dynamics of modern family life. The application of maqasid al-shariah in Aceh’s family courts demonstrates that Islamic law possesses the flexibility to address contemporary human concerns while preserving its theological integrity. Consequently, the maqasid-based adjudication paradigm offers an alternative model for Indonesia’s Islamic legal system—one that harmonizes scriptural principles with social realities and ethical objectives.